Zoonotic bacteria in clinically healthy goats in petting zoo settings of zoological gardens in Germany. (28th February 2022) - Göttling, Jannis; Heckel, Jens‐Ove; Hotzel, Helmut; Fruth, Angelika; Pfeifer, Yvonne; Henning, Klaus; Kopp, Peter; Mertens‐Scholz, Katja; Rietschel, Wolfram; Pfeffer, Martin
Abstract: Goats and other small ruminants are frequently used as contact animals in petting zoo settings of zoological gardens. However, they are capable to carry a broad spectrum of zoonotic pathogens without clinical signs. In this study, we analysed the presence of different zoonotic pathogens in 300 clinically healthy goats from 14 zoological gardens in Germany. Rectal and nasal swabs were investigated with a series of cultural and molecular techniques. In addition, vaginal swabs of the 230 female goats were investigated for the presence of Coxiella burnetii by real‐time PCR. Antibodies against C . burnetii were tested in milk and serum by ELISA. Campylobacter spp. were found in 22.7%, Shiga‐toxigenic Escherichia coli in 20.0% and Arcobacter spp. were found in 1.7% of the tested 300 goats after culture from rectal swabs and subsequent PCR. One sample contained an Escherichia fergusonii isolate with a bla CTX‐M‐1 ‐encoded extended‐spectrum beta‐lactamase phenotype. Neither Yersinia spp. nor Salmonella spp. were found. Nasal swabs of 20.7% of the goats yielded Staphylococcus aureus including one mec C‐positive methicillin‐resistant isolate. Neither Yersinia spp. nor Salmonella spp. were found, and none of the 230 vaginal swabs was positive for C . burnetii . Attempts to detect dermatophytes failed. In conclusion, a possible risk of transmission of zoonotic bacteria from goats in petting zoos to visitors should be considered. Appropriate information and facilities for hand washing and disinfection should be provided in all zoological gardens using goats as contact animals due to the regular presence of zoonotic bacteria in the collection.